Participation of civil society in new modes of governance: the case of the new EU member states. Part 2: Questions of accountability - Forschungsstelle Osteuropa an der Universität Bremen (2006)
Abstract: "This working paper is part of a series presenting the results of a research team examining theimpact of the 2004 EU enlargement on governance structures involving the participation of civilsociety organisations. The working paper starts with a contribution by David Lane summarizing the state of civil society organisations in the post-socialist EU member states and their potential for an active role in new modes of governance. He offers a quantitative and qualitative assessment and discusses the implications for questions of accountability. The following two articles by Zdenka Mansfeldová and Micha? Federowicz and Micha? Sitek go on to elaborate on civil society organisations holding state actors accountable. Mansfeldová examines the societal context for political and administrative accountability in the Czech Republic, while Federowicz and Sitek examine the political accountability of the Polish government. The next two contributions focus on state actors holding civil society org